2016
DOI: 10.1007/s12105-016-0771-0
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Rhabdomyosarcoma: Clinical and Pathologic Characterization of Seven Cases

Abstract: were observed, suggesting aggressive clinical behavior regardless of subtype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…Prior studies investigating rhabdomyosarcoma demographics and prognostic factors using databases have largely focused on specific anatomic sites or JOURNAL OF ORTHOPAEDIC RESEARCH ® OCTOBER 2019 subtypes. 3,4,6,[14][15][16][17][18][19][20] In a 2017 study by Nasioudis et al 15 rhadomyosarcoma of the lower female genital tract was shown to be most prevalent in prepubertal girls and adolescents, but carry excellent survival rates. Additionally, rare cases affecting adults resulted in poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies investigating rhabdomyosarcoma demographics and prognostic factors using databases have largely focused on specific anatomic sites or JOURNAL OF ORTHOPAEDIC RESEARCH ® OCTOBER 2019 subtypes. 3,4,6,[14][15][16][17][18][19][20] In a 2017 study by Nasioudis et al 15 rhadomyosarcoma of the lower female genital tract was shown to be most prevalent in prepubertal girls and adolescents, but carry excellent survival rates. Additionally, rare cases affecting adults resulted in poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The incidence is greatest in young adults under the age of 20, with an incidence rate of 4.4 cases per one million. 3 Incidence decreases with age, representing only 1% of adult solid tumor malignancies. [4][5][6] Most cases occur sporadically, although genetic conditions such as Li-Fraumani syndrome and Neurofibromatosis type 1 are associated with increased risk.…”
mentioning
confidence: 99%
“…Rarely, it is confused with other benign lesions such as myositis ossificans, pyogenic myositis. Beside this non-Hodgkin lymphoma, neuroblastoma, Ewing sarcoma familial tumors, acute myeloid leukemia, Langerhans cell histiocytosis should be considered in the differential diagnosis of rhabdomyosarcoma (2,4,7). The gold standard diagnostic method in soft tissue mass is histopathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the overall clinical presentation of a painless, rapidly enlarging, recurrent maxillary growth along with the histopathological features, our differential diagnosis included a broad spectrum of neoplasms from small round-cell neoplasms such as RMS, extraosseous ewing sarcoma (ES), lymphoma or olfactory neuroblastoma to spindle cell tumour-like fibrosarcoma or spindle cell carcinoma 6 9…”
Section: Differential Diagnosismentioning
confidence: 99%
“…The commonly affected sites are the head and neck region, genitourinary tract, retroperitoneum, extremities, trunk, chest, perineum and gastrointestinal tract 3 7 8 . The head and neck region is commonly involved in children, whereas in adults, the trunk and extremities are mainly affected 7 9 10. Areas involved in the head and neck region are divided into three main groups, cranial parameningeal, orbital and non-orbital–non-parameningeal which accounts for 35%–40% of all RMS cases, of which 10%–12% cases involve the oral cavity, with an affinity for the palate, tongue, lips and buccal mucosa 1 3 7 8 11–13.…”
Section: Introductionmentioning
confidence: 99%